2022
DOI: 10.1007/s10209-022-00936-1
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of smart home voice assistant: a comparison among younger, middle-aged, and older adults

Abstract: Voice assistants are widely used in smart home environments. This study aimed to investigate user acceptance of a smart home voice assistant. A questionnaire was designed, and 471 Chinese adults were recruited to complete the questionnaire. The data were analyzed using exploratory factor analysis and regression analysis. The results revealed that user requirements of adults were composed of six factors: hedonic motivation and trust ( β = .41, p < .001), social infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
4
4
0
Order By: Relevance
“…Consequently, older adults may be inclined to embrace VAs due to their perception of VAs as valuable and convenient technologies. Furthermore, results also showed a positive impact of perceived enjoyment on behavioral intention, which was consistent with previous research on VAs ( Nguyen et al, 2018 ; Zhong et al, 2022 ). As older adults perceive time as limited, they prioritize emotional satisfaction over other goals ( Carstensen, 1995 ), and positive user emotions and experiences contribute to their acceptance of the product.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consequently, older adults may be inclined to embrace VAs due to their perception of VAs as valuable and convenient technologies. Furthermore, results also showed a positive impact of perceived enjoyment on behavioral intention, which was consistent with previous research on VAs ( Nguyen et al, 2018 ; Zhong et al, 2022 ). As older adults perceive time as limited, they prioritize emotional satisfaction over other goals ( Carstensen, 1995 ), and positive user emotions and experiences contribute to their acceptance of the product.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…This study categorized the factors influencing the acceptance of VAs among older adults into VAs product characteristics and personal characteristics of older adults. Consistent with previous research, it was observed that perceived usefulness, perceived enjoyment, and technological self-efficacy significantly affected behavioral intention ( Nguyen et al, 2018 ; Song et al, 2022 ; Zhong et al, 2022 ). However, there were several differences between the model created and the results produced by existing research.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 3 more Smart Citations